Peran Pemahaman Fiqh Muamalah dan Literasi Akuntansi dalam Pemilihan Produk Pembiayaan Murabahah - Dwiya Endah Pandu Probowati; Anis Chariri; Jaka Isgiyarta (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
Murabaha sharia financing is a famous product for sharia financial institutions. This study aims to obtain information related to the role of understanding fiqh muamalah and accounting literacy in the selection of Murabahah financing products at BMT ABC at Cirebon Regency. This study uses a qualitative interpretive case study method to gain an in-depth understanding of an event so that a research conclusion can be drawn that will provide benefits. The main findings in this study are the low understanding of Islamic fiqh muamalah and the absence of accounting literacy causing BMT ABC customers to choose Murabahah financing for all financing purposes.